Models for Bank Risk Regulation - Dynamics Modelling and Prospects - Feschiyan, Daniela; Andasarova, Radka (Research Papers, 2020)
The Standardized Approach (SA) for credit risk assessment is a positive asset in bank capital regulation in contemporary banking. The revisions to the regulatory framework – Basel III by the Basel Committee on Banking Supervision is a long continuous process influenced by numerous economic, social and political factors. The present article shows the modern aspects of credit risk regulation in banks within Basel III: Finalising post-crisis reforms. The study presents the development and chronology of the global regulatory frameworks for banks - Basel I, Basel II and Basel III. The theoretical interpretation of the proposed new standardized approach for risk modeling in banks is reviewed.